2012
DOI: 10.2166/wst.2012.300
|View full text |Cite
|
Sign up to set email alerts
|

Towards a generalized physicochemical framework

Abstract: Process models used for activated sludge, anaerobic digestion and in general wastewater treatment plant process design and optimization have traditionally focused on important biokinetic conversions. There is a growing realization that abiotic processes occurring in the wastewater (i.e. 'solvent') have a fundamental effect on plant performance. These processes include weak acid-base reactions (ionization), spontaneous or chemical dose-induced precipitate formation and chemical redox conversions, which influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…The model by Hellinga et al (1999) included pH calculations based on acid-base equilibria only. However, for a realistic modeling of pH in high strength wastewaters ion activity and complex formation have to be considered as well (Batstone et al, 2012). This is definitely the case for source-separated urine (Udert et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…The model by Hellinga et al (1999) included pH calculations based on acid-base equilibria only. However, for a realistic modeling of pH in high strength wastewaters ion activity and complex formation have to be considered as well (Batstone et al, 2012). This is definitely the case for source-separated urine (Udert et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…A good example of such approach can be found in Vaneeckhaute et al [90] that developed a generic nutrient model in order to optimize nutrient (N, P) and energy recovery of treatment facilities with a focus on fertilizer quality and quantity. Batstone et al [91] showed that there is a serious need of improvement on current physicochemical models for them to be applied for nutrients recovery purposes.…”
Section: Considerations On the Energy-nutrient Nexus In Wwtpsmentioning
confidence: 99%
“…Sewage treatment using MFC systems in European Union could save up to 1 M tonne/year, and a considerable amount of sludge disposal costs [100,101]. Bio-electrochemical systems could also be implemented for the integration of energy and nutrients recovery: there have been, in fact, interesting studies on the possibility of phosphorus recovery in the form of struvite by MFC systems [91,102]. Studies suggest that phosphorus could be removed up to 82% by MFC systems, 40% of which it could be recovered as struvite [103].…”
Section: Considerations On the Energy-nutrient Nexus In Wwtpsmentioning
confidence: 99%
“…In this respect, the use of mathematical models for nutrient and energy recovery can be very valuable for optimization of both process performance and fertilizer quality. As up to date an adequate integrated biological-physicochemical modelling approach for resource recovery is lacking (Batstone et al, 2012), the development and use of such prototype models will be aspect of further research.…”
Section: Fertilizer Markets Legislations and Recommendationsmentioning
confidence: 99%